Livros didáticos de cursos de redação empresarial: textos e contextos - Pereira, Lucília de Macedo (2008)
This study presents one analysis, by the dialogical perspective of language, (Bakhtin & Volochinov, 1929/2004; Bakhtin, 1979/2003) of two didactic books: Composition and Grammar for the corporate world, by Laurinda Grion (São Paulo: Grion, 2006), and Corporate Composition, by Márcia Moreira Borges research of content and composition - and Maria Cristina Baeta Neves methodological treatment (Rio de Janeiro: Senac Nacional, 1997), used in short term free courses of Corporate Composition (CC). This research aims at contributing to the studies of corporate language in the didactic books of CC in the scope of Applied Linguistics and Language Education. The questions that direct this study are: How does the sphere of circulation of didactic books used in free courses of corporate composition selected for this research is constituted? What contents (in relation to corporate genre and grammar) are developed and how are they treated? What are the ways of discourse s construction of the authors in the selected books? How is the other s presence built and what is is the role of it in the authors discourse? This research is grounded in the inseparable relation of language and human activity and in the notion of discursive genre. Besides that, this study is contextualized in the research area of Language and Work, as it is developed in the Program of Post-Graduate Studies in Applied Linguistics and Language Education of Pontifícia Universidade Católica de São Paulo. The methodology used to make this research feasible was rooted in the bakhtinian proposal for the study of language, based on a socio-historical perspective. In both analyses it has been observed that these books are characterized by the treatment of linguistical phenomena very briefly, standardized, fragmented and out of context. The discourse of the authors is directed to the construction of procedures and recommendations, mirroring renowned literary writers, with a strong typological worry, with focus on old fashioned or/and non-authentical models. The discursive questions of the corporate sphere practically do not have relevance in the corpus studied